A pan-cancer analysis of homeobox family: expression characteristics and latent significance in prognosis and immune microenvironment - Yuanhui Wang; Jie Gao; Ziyi Ren; Ziyi Shen; Wei Gu; Qinyi Miao; Xiaomeng Hu; Xiaomeng Hu; Yan Wu; Yan Wu; Wei Liu; Jia Jia; et al. (Frontiers in Oncology)
BackgroundThe Homeobox (HOX) gene family are conserved transcription factors that are essential for embryonic development, oncogenesis, and cancer suppression in biological beings. Abnormally expressed HOX genes in cancers are directly associated with prognosis.MethodsPublic databases such as TCGA and the R language were used to perform pan-cancer analyses of the HOX family in terms of expression, prognosis, and immune microenvironment. The HOX score was defined, and potential target compounds in cancers were predicted by Connective Map. Immunohistochemistry was employed to validate protein expression levels. Gene knockdowns were used to verify the effects of HOXB7 and HOXC6 on the proliferation and migration of lung adenocarcinoma (LUAD) cells.ResultsHOX genes play different roles in different cancers. Many HOX genes, especially HOXB7 and HOXC6, have higher expression and lower overall survival in specific cancers and are predicted as risk factors. The high expression of most HOX genes is mainly related to immune subtypes C1-C4 and C6. Potential anti-tumor compounds for down-regulating HOX gene expression were identified, such as HDAC inhibitors and tubulin inhibitors. LUAD Cell migration and proliferation were inhibited when HOXB7 or HOXC6 was knocked down.ConclusionsMany HOX genes may act as both oncogenes and tumor suppressor genes, necessitating precision medicine based on specific cancers. The HOX gene family plays a crucial role in the development of certain cancers, and their expression patterns are closely related to cancer prognosis and the tumor microenvironment (TME), which may affect cancer prognosis and response to immunotherapy. Compounds that are negatively correlated with the expression levels of the HOX family in various cancers, such as HDAC inhibitors, are potential anti-cancer drugs. HOXB7 and HOXC6 may serve as potential targets for cancer treatment and the development of targeted compounds in the future.